2021
DOI: 10.18332/ejm/137664
|View full text |Cite
|
Sign up to set email alerts
|

Slovenian midwifery professionalization: Perception of midwives and related health professions

Abstract: INTRODUCTION This article presents research into the professionalization of midwifery in Slovenia. Since recognition by related occupations is important for professions, this comparative study asked doctors and nurses in Slovenia about their perceptions of the status of midwifery. METHODS A questionnaire survey was conducted with 300 Slovenian midwives, 666 nurses and 416 obstetricians. The questionnaire included statements covering traditional sociological notions of the profession (ethics, theory, power), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The Regulation of the Minister of Labour and Social Policy on the Classification of Professions and Specialties classifies midwives into the category of ‘specialists’ regardless of whether they have reached the highest education level 19 . A study by Mivsek et al 20 confirmed that the awareness of the rank of the profession had a positive impact on cooperation and relations between professions.…”
Section: Discussionmentioning
confidence: 95%
“…The Regulation of the Minister of Labour and Social Policy on the Classification of Professions and Specialties classifies midwives into the category of ‘specialists’ regardless of whether they have reached the highest education level 19 . A study by Mivsek et al 20 confirmed that the awareness of the rank of the profession had a positive impact on cooperation and relations between professions.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely in Flanders and the Netherlands, midwifery education have identified professional autonomy as an essential part of additional advanced professional skills (Mestdagh et al, 2019). As maternity care HPs are poorly aware of each other's competencies, (Mivšek et al, 2021) recommend interprofessional education to promote interdisciplinary collaboration in maternity care while retaining autonomy within each profession.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Additionally, their influence on healthcare systems and policymaking raised further considerations [ 8 ]. Midwives’ professional autonomy seems to be particularly limited and they face barriers in fulfilling a comprehensive role as legally defined by the European Directives on the scope of midwifery in Europe [ 9 ]. Midwifery autonomy, a cornerstone of professional practice, has been almost completely relinquished within obstetric-led care in some countries [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interprofessional collaboration is only possible when the different professionals respect each other and are in equal positions. In Slovenia, for example, midwives, nurses and obstetricians are poorly aware of each other’s roles and competencies, and obstetricians do not recognize midwives as autonomous professionals for normal pregnancy, birth and postpartum [ 9 ]. A study exploring interprofessional collaboration between midwives and obstetricians in hospitals in Canada demonstrated willingness from the obstetricians to work collaboratively with midwives.…”
Section: Introductionmentioning
confidence: 99%